Kajian Efektivitas Taman Pandanaran Berdasarkan Opini Pengunjung - Maulida Kurniadewi; Parfi Khadiyanta (Ruang, 2018)
Implementation of the program from Dinas Kebersihan dan Pertamanan Semarang City related to increase of active park as green open space and family recreation facility that is the development of Taman Pandanaran. The location of the park which was inaugurated early in 2015 was strategic so that became the center of connector icon of Semarang City that is Simpang Lima, Taman Menteri Supeno, Tugu Muda, and GOR Tri Lomba Juang. Built as active garden concept, visitors can take advantage of the park for a variety activites such as social, recreational, and sports. The park that cost 1.866 billion rupiah is one of the public space of Semarang City as the capital of Central Java, then it is appropriate to give satisfaction to the park’s visitors. This study aims to assess the effectiveness of Taman Pandanaran based on visitor opinion. The research method used is descriptive quantitative analysis by using questionnaire as information digging tool. The results of this study indicate that the effectiveness of Taman Pandanaran based on visitor opinion is quite effective with the score of 152 from the total score of 225. Each variable contribute different scores ranging from the highest to the lowest score. The most effective variable is that it can be used throughout the community, while the comfortable environment is the lowest rated variable. It describes the existing condition in the environment of Taman Pandanaran which gives less comfort to the park visitors.